2020
DOI: 10.3892/ol.2020.11518
|View full text |Cite
|
Sign up to set email alerts
|

Association of lncRNA‑p53 regulatory network (lincRNA‑p21, lincRNA‑ROR and MALAT1) and p53 with the clinicopathological features of colorectal primary lesions and tumors

Abstract: Colorectal cancer (CRC) is a common intestinal cancer with a high mortality rate. Early detection of this type of cancer is fundamental to the prevention of the disease, which results in improved survival rates. In the human colon tissue, transition from normal epithelium to adenoma is considered to be caused by unknown molecular incidents occurring over 5-10 years. The detection of CRC has proved problematic when in the early stages of disease. In addition, identifying suitable biomarkers for the detection of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 41 publications
0
15
0
Order By: Relevance
“…However, no association with neither OS nor metastasis-free survival were found, maybe due to the reduced number of patients. However, in a more recent study [ 24 ] in 66 CRC patients, no significant differences were observed between tumor and adjacent normal tissue and lincRNA-p21 levels, but they found using ROC curve analysis that lincRNA-p21 could have an impact as diagnostic marker (AUC tumor versus normal tissue of 0.796). The prognosis impact was not studied in that work.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…However, no association with neither OS nor metastasis-free survival were found, maybe due to the reduced number of patients. However, in a more recent study [ 24 ] in 66 CRC patients, no significant differences were observed between tumor and adjacent normal tissue and lincRNA-p21 levels, but they found using ROC curve analysis that lincRNA-p21 could have an impact as diagnostic marker (AUC tumor versus normal tissue of 0.796). The prognosis impact was not studied in that work.…”
Section: Discussionmentioning
confidence: 92%
“…The prognosis impact was not studied in that work. Since lincRNA-p21 have been described as key element in the TP53 pathway, both papers studied the association with TP53 in patient samples, analyzing the correlation with TP53 mutational status [ 22 ] or the correlation with p53 mRNA levels [ 24 ]. However, no significant correlations with TP53 were observed in both papers.…”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, these results are not comparable with the present work since our correlation was obtained in tumor tissue isolated prior to adjuvant CRT treatment administration. Moreover, the two previous references focused on the potential role of lincRNA-p21 and radiotherapy response in relation to its role in the p53 pathway [ 21 , 30 , 31 , 32 ]; nonetheless, we cannot ignore that rectal cancer patients included in the cohort also received 5-fluorouracil. Lee and colleagues analyzed the pattern of lncRNAs in 5-fluorouracil-resistant colon cancer cell lines and observed that lincRNA-p21 was significantly upregulated in SNU-C5 5-FU-resistant cells compared to its parental cell line [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…It has been previously shown that lncRNAs contribute to GC development through several signaling pathways such as AKT and MAPK (23). Furthermore, interactions between lncRNAs and their target genes seem to affect pathogenic mechanisms in GC (24). Indeed, lncRNAs have a wide range of functions, including tumor growth sup-pression and oncogenesis regulation, and can act through a number of pathways (25).…”
Section: Discussionmentioning
confidence: 99%